Terms of address in Turkish pet-directed speech: Questionnaire vs. spontaneous production results - Nihan Ketrez, F. (Elsevier Ltd, 2024)
Terms of address in Turkish spontaneous pet-directed speech and those reported by the same pet-owners in questionnaires were compared with a focus on the proportion of diminutive and hypocoristic morphemes attached to various types of bases in order to see whether different data collection methods revealed different patterns of language use. The results showed that pet owners used diminutive and hypocoristic morphology along with the possessive marker in their spontaneous interactions to express endearment. While hypocoristic forms occurred with similar frequency in both sets of data, pet owners were less likely to report diminutives in their questionnaire responses although they used them in their spontaneous interactions. This is attributed to the use of diminutives to express the type of empathy, which could be easier to establish in spontaneous face-to-face communication. This attribution correctly predicted that stigmatized inverse address forms, as well, were rare in questionnaire responses. © 2024 Elsevier Ltd
Keywords: Address İnversion; Diminutive; Hypocoristics; Pet-Directed Speech; Possessive; Turkish